Last One To Die - Murphy, Cynthia, (YA author) (New York : Delacorte Press, 2021)
"Sixteen-year-old, Irish-born Niamh has just arrived in London for the summer, and quickly discovers that girls who look frighteningly like her are being attacked"--.
Ages 12 and up.
Keywords: Supernatural -- Fiction; Horror stories; Stalking -- Fiction; Murder -- Fiction; Interpersonal relations -- Fiction; Irish -- England -- Fiction; Novels; Romance fiction; Horror fiction